(untitled) (Confluenţe Bibliologice, 2020)
The book was published in 1905 at Bucharest, Socecu Publishing House and is illustrated beautifully with images from Wolkenberg’s postcards from Chisinau. It is a facsimile reproduction made by Publishing House , Semne” of the original work. But the ﬁrst image shows a reproduction after a lithograph from 1837, executed by Raﬀet, titled Bessarabian Mail Cart.